Evaluation of tubomanometry as a routine diagnostic tool for chronic obstructive Eustachian tube dysfunction. (December 2015) - Schröder, S.; Lehmann, M.; Korbmacher, D.; Sauzet, O.; Sudhoff, H.; Ebmeyer, J.
Abstract : Objective: The objective of this study was to demonstrate the reliability of tubomanometry (TMM) described by Estéve in the diagnosis of chronic obstructive Eustachian tube (ET) dysfunction. Study design: Combined prospective and retrospective clinical study. Setting: Tertiary referral centre, affiliated to university. Methods: Two hundred and fifteen healthy subjects were examined once, 25 healthy subjects underwent TMM weekly for 6 weeks, and six healthy subjects were tested three times a day on at least three different days. The results of tubomanometry in healthy subjects were compared to data obtained from 171 patients with chronic obstructive ET dysfunction. Results: In healthy subjects, there was an immediate opening of the ET at 30–50 mbar with an R‐value ≤1 in at least 94% of the cases. In patients with chronic ET dysfunction, an opening of the ET could be registered in only 42% of patients at 30 mbar and in 58% at 50 mbar. The average of the R‐value in these subjects always indicated towards a delayed opening (R > 1). When measurements are repeated in the same subject with a weekly interval, the intraclass correlation (ICC) was 0.49 for the TMM with 30 mbar, 0.51 for the TMM with 40 mbar and 0.52 for the TMM with 50 mbar in healthy people. For the patients with symptoms of ET dysfunction, the ICC for up to four repeated measures was 0.50 for the TMM with 30 mbar, 0.53 for the TMM with 40 mbar and 0.54 for the TMM with 50 mbar. A complete agreement of the results in repeated measurements within seconds was present in 86% for 30 and 40 mbar and in 79% for 50 mbar. The ICC was 0.61 for the TMM with 50 mbar, 0.62 for the TMM with 40 mbar and 0.68 for the TMM with 30 mbar. Conclusions: Tubomanometry can support the diagnosis of ET dysfunction. An R‐value ≤1 indicates a regular function of the ET, an R‐value >1 indicates a delayed opening of the ET, and no definable R‐value means no detectable opening of the ET. TMM is a reliable and valid instrument to support the diagnosis of chronic obstructive ET dysfunction.